Policy instruments for creating markets for biodiversity: Certification and ecolabing - Paulo A. L. D. Nunes; Yohanes E. Riyanto (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper provides an economic evaluation of certification and ecolabeling as an important policy instrument for creating markets for biodiversity. In the paper we conclude that the success of a policy instrument for creating markets for biodiversity depends on the nature crucial factors, including the ability of the policy instrument to deal with (a) the public good nature of most of the nonmarket biodiversity benefits; (b) the asymmetric informational characteristics related to the biodiversity (and environmental friendly) market supply and demand mechanisms; (c) the impact of certification practices in the producer's costs, and (d) the cross price elasticity between regular and market certified products. Indeed, in some cases certification and ecolabeling policy instruments alone are not sufficient to guarantee a successful creation of markets for biodiversity. Finally, the certification schemes need to be sufficiently flexible to allow mutual recognition among the countries involved, as well as to meet the demand of weak sensitive markets. By mutual understanding, and learning with the past experiences, certification and ecolabeling will positively contribute to the creation of markets for biodiversity and thus expected to assist to the development of an effective and broadly accepted sustainable management of such a scarce natural resource.
Keywords: Q20; L50; 330; Biodiversity; regulation; certification; ecolabeling; information; adverse selection; consumer awareness; command-and-control; Artenvielfalt; Marktversagen; Umweltpolitik; Umweltzeichen; Welt